2017
DOI: 10.3389/fimmu.2017.00232
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Induction of an Idiotypic Cascade by Anti-Glycosaminoglycan Monoclonal Antibody in apoE−/− Mice: Association with Atheroprotection

Abstract: Atherosclerosis, the underlying pathology of most cardiovascular diseases, is triggered by the retention of apolipoprotein B (apoB)-containing lipoproteins in the arterial wall through electrostatic interactions with glycosaminoglycan (GAG) side chains of proteoglycans. Previously, we reported the antiatherogenic properties of the chimeric monoclonal antibody (mAb) chP3R99-LALA, which binds sulfated GAGs, inhibits low-density lipoprotein (LDL)–chondroitin sulfate (CS) association, and abrogates LDL oxidation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…28 In a rabbit and an apoE ¡/¡ mouse model, an affinity enhanced P3 antibody with the ability to inhibit LDL-chondrotin sulfate association, induced an active anti-chondroitin sulfate antibody response, preventing the formation of, and arresting the progression of atherosclerosis. [29][30][31] In our patients, the ability to mount a spontaneous anti-GD2 response was negatively influenced by the HAHA response but not by hu3F8 dosage level. Patients with positive HAHA (resulting in fewer treatment cycles received) had anti-GD2 response below the median.…”
Section: Discussionmentioning
confidence: 57%
“…28 In a rabbit and an apoE ¡/¡ mouse model, an affinity enhanced P3 antibody with the ability to inhibit LDL-chondrotin sulfate association, induced an active anti-chondroitin sulfate antibody response, preventing the formation of, and arresting the progression of atherosclerosis. [29][30][31] In our patients, the ability to mount a spontaneous anti-GD2 response was negatively influenced by the HAHA response but not by hu3F8 dosage level. Patients with positive HAHA (resulting in fewer treatment cycles received) had anti-GD2 response below the median.…”
Section: Discussionmentioning
confidence: 57%
“…Further research using chP3R99 in the same mouse model established the chP3R99-LALA variant restricted the progression of atherosclerosis in apoE À/À mice by preventing initial CS-LDL complex formation (Delgado-Roche et al 2015). Both the efficiency of the chP3R99-LALA mAb in initiating the anti-idiotype cascade and anti-atherogenic benefits were dose-dependent in apoE À/À mice but were independent of the sex and age of the mice (Sarduy et al 2017). The mAb was also shown to decrease inflammation and halt lesion development of advanced stages of atherosclerosis in male apoE À/À mice (Brito et al 2017).…”
mentioning
confidence: 91%
“…The chP3R99 mAb and the control hR3 continue to be generated at the CIM (54, 55). It has previously been reported that chP3R99 has the capacity to interfere with the development and progression of atherosclerosis in mice and rabbit models (3739, 46). In an extension to this work, we now demonstrate that chP3R99 can interfere with the interaction of both LDL and RM lipoproteins to vascular regions susceptible to atherogenesis in a rat model of IR.…”
Section: Discussionmentioning
confidence: 99%